Production and characterization of polygalacturonase from thermophilic Thermoascus aurantiacus on submerged fermentation - Martins, Eduardo da Silva [UNESP]; Ribeiro Leite, Rodrigo Simoes; da Silva, Roberto; Gomes, Eleni [UNESP] (Springer, 2012)
Microbial pectinase production by submerged fermentation (SMF) has been conducted mainly using mesophilic microorganisms. However, the use of thermophilic fungal strains capable of producing thermostable and thermophilic enzymes offers specific alternatives to biotechnology processes that use enzymes with such characteristics. Pectinases produced by thermophilic fungi may exhibit interesting characteristics, such as high thermostability, in terms of industrial application. Polygalacturonase (PG) production by the thermophilic fungus Thermoascus aurantiacus on SMF was carried out in culture media containing commercial pectin or agro-industrial by-products as carbon source under different fermentation conditions. The highest enzyme production occurred when the liquid waste from orange juice processing was used as substrate, after 5 days of cultivation. PG activity was highest when the fungus was cultivated at 45A degrees C with an initial pH of 5.5. PG showed an optimum temperature of 60A degrees C and optimum pH of 5.0. The enzyme showed greater stability in acid pH (3.0-4.5) and remained stable when incubated at 55A degrees C for 1 h.
Keywords: Thermoascus aurantiacus; Polygalacturonase; Submerged fermentation